Compressive Review on Novels of R. K. Narayan: Exploring the Literary and Artistic World of R. K. Narayan (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Narayan was one of Indo-Anglican's most successful writers, known for his works in Malgudi's fictional South Indian town. He is now viewed as pure literary artist, particularly when he is compared with Raja Rao Mulk Raj Anand, his two great contemporaries. He was compared with William Faulkner. His only goal is to provide aesthetic satisfaction and his is' art for the sake of the arts.' He does not write to spread his ideas on social or political problems, although when he began his literary career, Indian, under Mahatma Gandhi's leadership, was going through vital period of her fight for independence. Three of his novels have been published in quick successions, Swami Friends, Bachelor of Arts, and The Dark Room, and they have proved to be very successful.